2020
DOI: 10.1155/2020/2585960
|View full text |Cite
|
Sign up to set email alerts
|

Applying Complex Network and Cell‐Cell Communication Network Diagram Methods to Explore the Key Cytokines and Immune Cells in Local Acupoint Involved in Acupuncture Treating Inflammatory Pain

Abstract: Manual acupuncture (MA) can effectively treat a variety of diseases, but its specific mechanism remains unclear. The “acupoint network” activated by MA participates in MA signal transduction, in which immune-related cells and cytokines play an important role. However, which cells and cytokines in the acupoint have changed after MA? What is the network relationship between them? Which cells and cytokines may play the most important role in MA effect? These problems are unclear. In this study, on the basis of af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Fibroblasts and macrophages are the key cells that are stimulated with MA stimulation of the ST36 acupoint. 114 Gene chip assays revealed that the MA stimulation of ST36 modulates the expression of 236 genes and seven signaling pathways (ERK, P38, JNK, P53, BCR, TCR, and TLR receptor signaling), among which the ERK pathway was the most notable. 115 Apart from this, the upregulation of NF-κB signaling and the related cytokine gene expression (p-p65, p-p50, Nikbia, IL-1β, IL-6, CXCL1, CCL2, Rela, and NF-κB1) are also associated with ST36 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts and macrophages are the key cells that are stimulated with MA stimulation of the ST36 acupoint. 114 Gene chip assays revealed that the MA stimulation of ST36 modulates the expression of 236 genes and seven signaling pathways (ERK, P38, JNK, P53, BCR, TCR, and TLR receptor signaling), among which the ERK pathway was the most notable. 115 Apart from this, the upregulation of NF-κB signaling and the related cytokine gene expression (p-p65, p-p50, Nikbia, IL-1β, IL-6, CXCL1, CCL2, Rela, and NF-κB1) are also associated with ST36 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…MA at ST36 increased MCP-1, CXCL1, MIP-3α, MIP-1α, RANTES, IL-1β, IL-1α, IL-6, IL-2, IL-12, IL-13, granulocyte colony-stimulating factor (G-CSF), and M-CSF and decreased IL-18, IL-10, CRP, IFN-γ, GM-CSF, and percentage of CD45+CD11b+CD68+ cells in ST36 acupoint tissues. This study revealed the key changes of immune-related cells, cytokines, chemokines, and macrophages caused by MA and defined that MA effects are mediated by regulating cell–cell communication (CCC) networks ( 87 ). In another CFA-injected inflammatory pain model, ST36 MA increased TRPV1, TRPV4, ASIC3, PanX1, Cx43, and P2Y1 and decreased PGP 9.5 in muscle tissues at ST36.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al. treated the complete Freund’s Adjuvant (CFA)-induced inflammatory pain rats with manual acupuncture (MA), and they found that the inflammatory pain was significantly relieved, and the amounts of macrophages at acupoints were also raised in the experimental group ( 23 ). Interleukin (IL)-6, monocyte chemoattractant protein (MCP)-1, and IL-1 are important cytokines that have been identified by statistical and cytokine association networks.…”
Section: Acupuncture Modulates Innate Immune Cells’ Activitymentioning
confidence: 99%